Efektifitas Problem Based Learning (PBL) terhadap Kemampuan Pemecahan Masalah Mahasiswa pada Mata Kuliah Statistika Inferensia - Reni Untarti (AlphaMath : Journal of Mathematics Education, 2015)
This study is aimed to describe how the efectivenees of PBL to develope mathematical problem solving skill in inferensia statistics learning. This study was a quasi experiment conducted on the odd semester in the academic year of 2014/2015. The research population was all the 3th semester of mathematics education department, Muhammadiyah University of Purwokerto ion inferensia statistics topic. From the population, two classes were selected as the sample. The selected classes were Class III B and Class III C. Class III B dealt with the PBL, and class III B dealt with the direct instruction. The instrument to collect the data was an essay test to measure the mathematical communication and problem solving skills. Kolmogorove-smirnov test was used to test the normality of the data and to homogenity test using Levene’s Test. The data were analyzed using independent t-test. The results of the study show that PBL efective to develope mathematical problem solving skill of the 3th semester of mathematics education department student, Muhammadiyah University of Purwokerto in inferensia statistic learning. Kata Kunci: Mathematical Problem Solving Skill, Problem Based Learning